Poznavanje prve pomoči v primeru omrzlin med planinci, alpinisti in gorskimi reševalci - Slabe, Damjan (Šport (Ljubljana), 2018)
Introduction: Frostbite is tissue damage caused by outer temperature below 0 0C. When it comes to frostbite, proper first aid and the quickest possible transport of the injured to a health facility are of great importance to prevent further consequences of frostbite that could be more serious. Objective: discover the level of theoretical knowledge about frostbites, their prevention and first aid measures among mountaineers. Methodology: We used the descriptive method of work. The internet questionnaire completed 558 mountaineers from different Slovenian regions. Results and discussion: Respondents are more successful in recognizing chilblain than frostbite; they know preventive measures, body parts that are most exposed to frostbite, and risk factors; they can also distinguish between superficial and deep frostbites. The survey showed lower level of knowledge in giving first aid in a shelter. Mountaineers are more exposed to the risk of frostbite and hence they need to be properly informed and trained in giving frostbite first aid.
Keywords: dejavniki tveganja; omrzline; ozebline; preventiva; prva pomoč